Volunteering in environment conservation program: gain or loss - Wong, Li Juan; Lim, Evelyn Ai Lin; Bidin, Sheena; Mariapan, Manohar (Taylor & Francis, 2021)
Participation in an environmental conservation volunteer program provides secondary school students with the opportunity to establish a direct connection to their environment while contributing to the conservation of its natural heritage. The volunteering experiences also offer various forms of benefits to the volunteers as they ride through the challenges and learning experiences. A case study was conducted to explore the experiences of forty-five secondary school students who had volunteered in an environmental conservation volunteer program in the state of Perak. The study utilized focus group discussions to collect data. All discussions were audio-recorded and analyzed thematically using a two-layer constant comparative analysis method, triangulated using observations and reflection notes. Four themes emerged from the analysis to describe the benefits student volunteers gained from their active participation in the volunteer program. The challenges they experienced throughout their participation in the program were also described.